2016
DOI: 10.1556/030.63.2016.002
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated quinolone resistance among extended spectrum beta lactase producing Enterobacteriaceae from bloodstream infections

Abstract: The purpose of this study was to determine prevalence and molecular characterization of plasmid-mediated quinolone resistance (PMQR) genes [qnrA, qnrB, qnrC, qnrD, qnrS, aac(6′)-Ib-cr, qepA, and oqxAB] among extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella spp. isolates from bloodcultures in Hungary. A total of 103 isolates were tested for quinolone susceptibility by microdilution method and PMQR genes were detected by polymerase chain reaction. About 40 ESBLproducing E. coli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…This study found 17.7% prevalence of PMQR-positive Enterobacteriaceae from urine clinical sample and this is the first report of qnrD resistance determinant in Hungary. Earlier, investigation from Hungary showed extended-spectrum beta-lactamase (ESBL)-producing E. coli and Klebsiella spp., with qnrA, qnrB, qnrS, and aac(6)-Ib-cr [29,30]. Although we did not investigate the correlation of PMQRs in ESBL-producing strains, but based on our results, we can say that there is no strong correlation, as we found a total 38 strains being PMQR positive, but among them, only three showed resistance to third generation of cefalosporin.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This study found 17.7% prevalence of PMQR-positive Enterobacteriaceae from urine clinical sample and this is the first report of qnrD resistance determinant in Hungary. Earlier, investigation from Hungary showed extended-spectrum beta-lactamase (ESBL)-producing E. coli and Klebsiella spp., with qnrA, qnrB, qnrS, and aac(6)-Ib-cr [29,30]. Although we did not investigate the correlation of PMQRs in ESBL-producing strains, but based on our results, we can say that there is no strong correlation, as we found a total 38 strains being PMQR positive, but among them, only three showed resistance to third generation of cefalosporin.…”
Section: Discussionmentioning
confidence: 62%
“…According to international data, the prevalence of PMQR genes, qnrA, qnrB, qnrS, aac(6′)-Ib-cr, and qepA is associated with ESBLs, but actual prevalence of qnrC is unknown; however, some data are released about qnrD [6,17,30].…”
mentioning
confidence: 99%
“…Earlier studies demonstrated OqxAB efflux pump in extended-spectrum beta-lactamase-producing and fluoroquinolone-resistant K. pneumoniae high-risk clones [ 19 21 ]. In Hungary, K. pneumoniae with oqxAB resistance determinant was reported in bloodstream infections [ 22 ]. In all these reported studies, tested strains were resistant to fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, plasmid-mediated quinolone resistance determinants have been also reported among E. coli isolates, furthermore, plasmid-mediated fosfomycin-modifying enzymes, fosA3 and fosC2, were identified in E. coli clinical isolates. Acquisition of these fosfomycin resistance determinants, which inactivate fosfomycin by exerting glutathione-S-transferase activity, has also been seem to confer resistance [19,25]. Although phenotypic test reported eight isolates of E. coli as fosfomycin-resistant strains, molecular test showed that none of them had the fosA3 or fosC2 genes.…”
Section: Discussionmentioning
confidence: 99%